On a mechanical interpretation of self-energy in electrostatics and magnetostatics and an interpretation of Faraday’s law - Khanchong C. (2017)
© 2017, Chiang Mai University. All rights reserved. We use a consistency argument from a mechanical perspective to interpret the existence of electrostatic and magnetostatic self-energy. According to the magnetostatic self-energy introduced beforehand in this mechanical context, we can use the energy-conservation statement at the outset to interpret Faraday’s law. This approach to Faraday’s law reverses the typical arguments found in standard texts.